Bucerotidae from the early Miocene of Napak, Uganda (East Africa): the earliest hornbill with a modern‐type beak. (22nd December 2020) - Riamon, Ségolène; Pickford, Martin; Senut, Brigitte; Louchart, Antoine
Abstract : Hornbills (Bucorvidae and Bucerotidae) are among the most recognizable groups of birds. Their large, curved beak topped by a casque is their most obvious feature. Here, we describe the earliest fossil of a hornbill, and more precisely a Bucerotidae, from the early Miocene of Napak, Uganda. This fossil is a proximal part of a maxilla that can be tentatively assigned to the genus Tockus and which attests to an ancient evolutionary origin of this particular beak shape. The new fossil, as well as several postcranial bones, represents the earliest record of the Bucerotidae dated to about 19 million years ago, and can serve as a calibration point in future molecular phylogenies.